CLINICAL PHARMACOLOGICAL APPROACH TO THE USE OF ANTI-INFLAMMATORY DRUGS IN PREGNANCY - Usmonova Feruza Tokhirjonovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article examines the clinical pharmacological principles guiding the safe and evidence-based use of anti-inflammatory drugs during pregnancy. It focuses on the pharmacokinetic and pharmacodynamic changes occurring in pregnant women, the risk–benefit assessment of non-steroidal anti-inflammatory drugs (NSAIDs), corticosteroids, and selective anti-inflammatory agents, as well as the potential fetal and maternal outcomes associated with inappropriate therapy. The paper also highlights current international recommendations, contraindicated drugs, trimester-specific considerations, and clinical monitoring strategies that ensure optimal therapeutic outcomes while minimizing teratogenic and obstetric risks.